Kewirausahaan Perspektif Hadis: Studi Takhrij dan Syarah - Rycho Nur Nirbita Sias; Dadah (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the implementation of entrepreneurship in the hadith. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about the implementation of entrepreneurship in the hadith narrated by Ibn Majah No. 2237. The results and discussion of this study indicate that the status of quality hadith hasan li ghairihi that meets the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the hadith narrated by Ibn Majah no. 2237 is relevant to be used as knowledge to shape the nature and character in the field of entrepreneurship.